2014
DOI: 10.1523/jneurosci.0313-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

The Acquisition of Goal-Directed Actions Generates Opposing Plasticity in Direct and Indirect Pathways in Dorsomedial Striatum

Abstract: A cortical-basal ganglia network involving, particularly, the posterior region of dorsomedial striatum (DMS) has been implicated in the acquisition of goal-directed actions; however, no direct evidence of learning-related plasticity in this striatal region has been reported, nor is it known whether, or which, specific cell types are involved in this learning process. The striatum is primarily composed of two classes of spiny projection neurons (SPNs): the striatonigral and striatopallidal SPNs, which express d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
111
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(120 citation statements)
references
References 35 publications
6
111
1
Order By: Relevance
“…It is conceivable that D1-MSN clusters encode information that facilitates locomotion, and D2-MSN clusters encode information that inhibits unwanted locomotion, and coordination of D1- and D2- MSN clusters form cell assemblies that guide locomotion sequences. Notably, beyond the opposite aspect of locomotion regulation proposed by the longstanding model of striatal direct and indirect pathway, such opposing roles for direct and indirect pathway neurons have also been suggested in reward and punishment (Kravitz et al, 2012), in goal-directed behavior (Shan et al, 2014; Sippy et al, 2015; Tai et al, 2012), and in mechanisms influencing primary motor cortex (Oldenburg and Sabatini, 2015). We therefore speculate that similar coordinated activities of neural clusters in the direct and indirect pathways of dorsal striatum may also encode other striatal-controlled behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that D1-MSN clusters encode information that facilitates locomotion, and D2-MSN clusters encode information that inhibits unwanted locomotion, and coordination of D1- and D2- MSN clusters form cell assemblies that guide locomotion sequences. Notably, beyond the opposite aspect of locomotion regulation proposed by the longstanding model of striatal direct and indirect pathway, such opposing roles for direct and indirect pathway neurons have also been suggested in reward and punishment (Kravitz et al, 2012), in goal-directed behavior (Shan et al, 2014; Sippy et al, 2015; Tai et al, 2012), and in mechanisms influencing primary motor cortex (Oldenburg and Sabatini, 2015). We therefore speculate that similar coordinated activities of neural clusters in the direct and indirect pathways of dorsal striatum may also encode other striatal-controlled behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…The DMS is important in goal-directed behavior such as reward motivated learning, and differential plasticity in dMSNs and iMSNs is an important contributor to such learning (Shan et al, 2014). While the differential activation and inhibition of dMSNs and iMSNs by dopamine acting via D 1 and D 2 receptors has received great attention, it is possible that other neurotransmitters, including serotonin, also impact striatal learning by their balanced or imbalanced activity differentially activating these pathways (Kravitz et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Plasticity of any inputs converging on the striatum that differentiates between the direct and indirect pathway could presumably mediate reinforcement learning to bias future action selection. Recent evidence shows differential plasticity of inputs onto these two pathways: Shan and colleagues (2014) showed that training in a goal directed task alters the AMPA to NMDA ratio of glutamatergic synapses onto the direct and indirect pathway MSNs in opposite directions in mice (Shan et al, 2014). Plastic changes onto striatal direct and indirect pathway neurons may thus serve a vital function dynamically linking ‘states of the world’ to motor responses that bring the highest value rewards.…”
Section: The Role Of the Direct And Indirect Pathway In Action Selectionmentioning
confidence: 99%
“…Recent evidence suggest that chemical genetic inhibition of orbitofrontal inputs to striatum can disrupt while optogenetic stimulation can enhance goal-directed behavior (Gremel and Costa, 2013). As mentioned above, the type of behavioral biases tied to these representations may similarly be tied to their relative balance of inputs onto direct and indirect pathway MSNs also acquired through a process of learning (Shan et al, 2014). The predicted enhancement of synaptic strength could potentially be studied in vivo using novel methods to couple electrophysiological (Znamenskiy and Zador, 2013) or optical measurements of specific striatal inputs (Gunaydin et al, 2014) while simultaneously utilizing methods similar to Cui, et al 2014 and Jin, et al 2014 to record the activity in downstream basal ganglia subcircuits and motor outputs.…”
Section: Future Directions: Following Iterative Processes Of Integratmentioning
confidence: 99%